Gus Miftah's Da’wa Language Style in Youtube Video - Aziz, Moh. Ali; Nadzario, Amanda Putri; Arif, Rozaqul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
This paper examines, (1) How is the choice of words used by Gus Miftah in the Youtube video entitled the commemoration of the Islamic New Year 1441 Hijriyyah at the Al-Qodiri Islamic Boarding School in Lampung? (2) What is the tone of voice used by Gus Miftah in the Youtube video entitled New Year's Commemoration? Islam 1441 Hijriyyah at the Al-Qodiri Islamic Boarding School in Lampung? (3) What is the sentence structure used by Gus Miftah in the Youtube video entitled Commemoration of the Islamic New Year 1441 Hijriyyah at the Al-Qodiri Islamic Boarding School in Lampung? Researchers used descriptive qualitative methods to obtain data. Then the data was analyzed using the analysis of the Miles and Huberman model. The results of this study are Gus Miftah's da’wa language style based on word choices ranging from formal, informal and conversational language styles but the most dominant is informal and conversational language styles, language styles based on tone of voice using noble and powerful language styles and for language styles based on sentence structure using climatic or gradation language style. Further research is expected to have other research that focuses on Gus Miftah's rhetorical style or Gus Miftah's da’wa strategy.